Germline-encoded affinity for cognate antigen enables vaccine-amplification of a human broadly neutralizing response against influenza virus - Sangesland, Maya (Immunity, 2019)
Antibody paratopes are formed by hypervariable complementarity-determining regions (CDRH3s) and variable gene-encoded CDRs. The latter shows biased usage in human broadly neutralizing antibodies (bnAbs) against both HIV and influenza virus, suggesting the existence of gene-endowed targeting solutions that may be amenable to pathway amplification. To test this, we generated transgenic mice with human CDRH3 diversity but simultaneously constrained to individual user-defined human immunoglobulin variable heavy chain (V(H)) genes, including IGHV1-69, which shows biased usage in human bnAbs targeting the hemagglutinin stalk of Group 1 influenza A viruses. Sequential immunization with a stalk-only hemagglutinin nanoparticle elicited Group 1 bnAbs, but only in IGHV1-69 mice. This V(H)-endowed response required minimal affinity maturation, was elicited alongside pre-existing influenza immunity, and when IGHV1-69 B cells were diluted to match the frequency measured in humans. These results indicate that the human repertoire could in principle support germline-encoded bnAb elicitation using a single recombinant hemagglutinin immunogen.